2002
DOI: 10.1038/sj.bjc.6600297
|View full text |Cite|
|
Sign up to set email alerts
|

The bisphosphonate zoledronic acid impairs membrane localisation and induces cytochrome c release in breast cancer cells

Abstract: Bisphosphonates are well established in the management of cancer-induced bone disease. Recent studies have indicated that these compounds have direct inhibitory effects on cultured human breast cancer cells. Nitrogen-containing bisphosphonates including zoledronic acid have been shown to induce apoptosis associated with PARP cleavage and DNA fragmentation. The aim of this study was to identify the signalling pathways involved. Forced expression of the anti-apoptotic protein bcl-2 attenuated bisphosphonate-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 34 publications
6
70
2
5
Order By: Relevance
“…Inhibition of caspase 3 prevents osteoclast apoptosis. In keeping with previous reports in breast cancer lines, we found clear evidence that only ZOL was capable of caspase 3 activation.in our cell line (27).…”
Section: Mechanism Of Apoptotic Deathsupporting
confidence: 93%
See 2 more Smart Citations
“…Inhibition of caspase 3 prevents osteoclast apoptosis. In keeping with previous reports in breast cancer lines, we found clear evidence that only ZOL was capable of caspase 3 activation.in our cell line (27).…”
Section: Mechanism Of Apoptotic Deathsupporting
confidence: 93%
“…After ZOL exposure however, the distribution of MSH2 protein changed markedly and adopted a peri-nuclear and cytoplasmic distribution, figure 7. Similarly, for PARP-1, its fulllength form p116 exhibited an 81% decrease in the ZOL-treated sample and more than 400% increase in the PAM-treated sample, indicating a higher degree of (27), prostate cancer (28) and multiple myeloma (33), pancreas (24). We found evidence of significant antiproliferative effects in a range 10-100 mol, consistent with previous studies.…”
Section: Mechanism Of Apoptotic Deathsupporting
confidence: 90%
See 1 more Smart Citation
“…IPP is further metabolized endogenously into an ATP analogue ApppI, which is able to induce apoptosis in cells by inhibiting mitochondrial adenine nucleotide translocase (ANT), causing also a loss of the mitochondrial membrane potential [17,20]. Several studies have demonstrated that the interruption of the protein prenylation is a major contributor to the anticancer action of N-BPs [7,36,37], whereas the role and the significance of the additional mechanism of action, accumulation of IPP/ApppI, is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] Work in our centre with breast cancer cells provided early evidence that inhibition of the mevalonate pathway was again central to the Bisphosphonates in the prostate cancer setting JP Coxon et al observed apoptotic effects. 38 We recently published similar results for various prostate cancer cell lines, 35 and provided evidence that the resultant apoptosis was dependent on the activation of caspases. Unpublished work in our laboratory has confirmed an apoptotic effect on prostate cancer cells at concentrations that are likely to be physiologically relevant.…”
Section: Current Treatment Options For Bone Metastasesmentioning
confidence: 71%